Does it really make a difference? Health care utilization with two high deductible health care plans - Stefan Pichler; Jan Ruffner (ETH Zurich, KOF Swiss Economic Institute, 2016)
Deductibles are commonly used to tame increasing health care costs. Numerous studies find that higher deductibles reduce health care utilization. In this paper we compare utilization in Switzerland between two health care plans with deductibles of 1,500 CHF and 2,500 CHF (1CHF = 1) per calendar year. While there is a minimum deductible level in Switzerland, individuals are free to increase their deductible and thereby reduce their insurance premium. In order to distinguish between selection and moral hazard we use regional variation in premiums as an instrument. Moreover, we take advantage of a policy change in 2005 that introduced the higher deductible for the first time. The results show that selection leads to considerable differences in utilization between the two groups, while we find no behavioral differences across both groups. If anything health care expenditures are higher for male individuals with the higher deductible, while for females there are no differences between the two deductible levels.
Keywords: I13; I12; C23; C26; 330; Health insurance; moral hazard; advantageous selection; deductible; instrumental variables